2017
DOI: 10.1016/j.enpol.2017.08.043
|View full text |Cite
|
Sign up to set email alerts
|

Large hydropower and legitimacy: A policy regime analysis, applied to Myanmar

Abstract: Title pageHIGHLIGHTS  First holistic analysis of hydropower policy legitimation struggles in Myanmar  Contention is necessary to re-legitimize a failing hydropower policy regime  A weakened or disrupted policy regime yields new opportunities for reform  We recommend inclusive stakeholder deliberation and multi-objective planning 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…One research work compared the more robust indigenous participatory mechanisms in Canada to those in Russia, where the development of the large Evenkiiskaya dam was halted partly due to active resistance from the indigenous community that was denied access to the official decision-making process [22]. Similar research on the Mekong [23] and rivers of Myanmar [24] has shown that the various facets in civil society that are denied access to decision-making may engage in developing their own disruptive strategies, including alternative assessment frameworks, and this may lead to drastic adjustments to project development processes driven by project proponents. Even companies strictly following national guidelines (and even best international practices) for public consultations during an EIA process still often experience fierce opposition from local communities, mainly when communities believe that the consultation process is being used as a tool to force hydropower projects in areas where communities do not agree in principle with dam building, or they see dams as a tool used by outside forces (e.g., central government) to impose control over territory/resources that local communities want to manage themselves [25].…”
Section: Importance Of Stakeholder Engagementmentioning
confidence: 99%
“…One research work compared the more robust indigenous participatory mechanisms in Canada to those in Russia, where the development of the large Evenkiiskaya dam was halted partly due to active resistance from the indigenous community that was denied access to the official decision-making process [22]. Similar research on the Mekong [23] and rivers of Myanmar [24] has shown that the various facets in civil society that are denied access to decision-making may engage in developing their own disruptive strategies, including alternative assessment frameworks, and this may lead to drastic adjustments to project development processes driven by project proponents. Even companies strictly following national guidelines (and even best international practices) for public consultations during an EIA process still often experience fierce opposition from local communities, mainly when communities believe that the consultation process is being used as a tool to force hydropower projects in areas where communities do not agree in principle with dam building, or they see dams as a tool used by outside forces (e.g., central government) to impose control over territory/resources that local communities want to manage themselves [25].…”
Section: Importance Of Stakeholder Engagementmentioning
confidence: 99%
“…Since 2011, Myanmar's partial and contested democratization [18] has led to a notable increase in technical assistance by international development partners, to multiple sectors. In turn, since 2017, such assistance has yielded an efflorescence of water and water-related studies (e.g., [3,[31][32][33]).…”
Section: Myanmarmentioning
confidence: 99%
“…We have shown the difficulties of trying to implement co-productive and collaborative models. Yet the alternative-managing complexity and contestation via bureaucratic modes of governance-offers no greater likelihood of planning outcomes legitimized by society (cf., [18]). Development partners instead can point to longstanding practices of collaborative planning in their own contexts.…”
Section: Conclusion: Advancing Collaborative Co-productive Iwrmmentioning
confidence: 99%
See 2 more Smart Citations